2017
DOI: 10.15291/geoadria.23
|View full text |Cite
|
Sign up to set email alerts
|

Prostorni raspored i gustoća ponikava jugoistočnog Velebita

Abstract: Dolines are considered to be among the most prominent karst formations, which is why they can serve as diagnostic forms of karst. Their spatial distribution and density are important indicators of an area’s degree of karstification, as well as of an overall geomorphological development. The aim of this paper is to determine the spatial distribution and the density of dolines, and also to analyse the influence of geological structure and morphometric features of the terrain (hypsometry, slope inclination, relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
(23 reference statements)
2
5
0
Order By: Relevance
“…This analysis thus indicates only a minor and localized influence of the fault on doline formation in the research area. Similar results were obtained from analogous research in SE Velebit (Marković et al, 2016) and on Slunj Plateau (Bočić et al, 2010). However, in this research only the most significant faults were considered.…”
Section: The Influence Of Geomorphometric Parameters and Geological F...supporting
confidence: 88%
See 2 more Smart Citations
“…This analysis thus indicates only a minor and localized influence of the fault on doline formation in the research area. Similar results were obtained from analogous research in SE Velebit (Marković et al, 2016) and on Slunj Plateau (Bočić et al, 2010). However, in this research only the most significant faults were considered.…”
Section: The Influence Of Geomorphometric Parameters and Geological F...supporting
confidence: 88%
“…In the east, the highest con- is low. Still, density of 30-34.23 dolines/km 2 could be considered as significant as it is in concordance with average doline density on Slunj karst plateau (42 dolines/ km 2 , Bočić et al, 2010) and higher than average density in mountainous regions: 27.5 dolines/km 2 in NW area of Velika Kapela (Pahernik, 2000), 19 dolines/km 2 in Northern Velebit and Senj ridge (Faivre, 1992(Faivre, , 1995, 18.4 dolines/km 2 in Biokovo (Bočić & Pahernik, 2011) and 10.6 dolines/km 2 in southeastern Velebit (Marković et al, 2016). Spatial distribution of dolines is important indicator of the karstification degree (Ford & Williams, 2007).…”
Section: Doline Spatial Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median planform area for the entire study territory is 711 m 2 . This provides an opportunity to compare Tara NP with other karst regions (e.g., Aggtelek Karst/Hungary, Telbisz (2001); Miroč/Serbia, Telbisz et al (2007); Velebit/Croatia, Marković et al (2016); Munții Pădurea Craiului/Romania, Telbisz et al (2015); Taurus/ Turkey, Öztürk et al (2018)). Based on this, it turns out that in the case of the Tara plateau the density is medium, and in the case of the other sub-areas the density is particularly low.…”
Section: Karst Morphologymentioning
confidence: 99%
“…Botanists have long recognised the valuable role of these habitats as ideal natural laboratories in which to study multiple environmental gradients, thermal stability and their effects on plant species composition and vegetation patterns. Studies have shown that dolines may provide microhabitats for unique plants that are rare or absent from the surrounding landscape (Beck von Mannagetta, 1906;Horvat, 1953;Kobal et al, 2015), further reinforcing the idea that these depressions can function as habitat islands (Özkan et al, 2010;Bátori et al, 2014Bátori et al, , 2017Su et al, 2017). In addition, the accumulation of cold-adapted plants (e.g., high montane and glacial relict species) within certain microhabitats of dolines -such as poleward-facing slopes and bottoms -is a prime indicator of the presence of current warm-stage microrefugia.…”
Section: Introductionmentioning
confidence: 99%